Migration in the Context of Climate and Environmental Changes within Central Asia and to the European Union and the Russian Federation - International Organization for Migration (United Nations, 2024)
This report focuses on the intersection of climate and environmental changes with movements within Central Asia as well as from Central Asia to the European Union and the Russian Federation. The report contributes to a growing body of literature on the matter, including movements affected by the slow- and sudden-onset impacts of climate change. The report identifies new trends in migration affecting the European Union and Central Asia and discusses the current state of legal and policy responses to these movements. It helps countries in the European Union and Central Asia fulfil commitments made in the Global Compact for Safe, Orderly and Regular Migration related to understanding the drivers of migration in the context of climate and environmental changes. The recommendations made in the report should also help European and Central Asian governments to develop policies that will enable them to respond to these movements more effectively.